Human Macrophages Escape Inhibition of Major Histocompatibility Complex-Dependent Antigen Presentation by Cytomegalovirus and Drive Proliferation and Activation of Memory CD4+ and CD8+ T Cells - Frascaroli, Giada; Lecher, Carina; Varani, Stefania; Setz, Corinna; van der Merwe, Johannes; Brune, Wolfram; Mertens, Thomas (Frontiers in Immunology, 2018)
Human cytomegalovirus (HCMV) persistently infects 50 to 90% of the human population but in the face of a normal immune system viral spread and dissemination are efficiently controlled thus preventing clinically signs and disease. HCMV-infected hosts produce a remarkably large amount of HCMV-specific CD4+ and CD8+ T cells that can even reach 20-50% of total T memory cells in the elderly. How HCMV may elicit such large and long-lasting T-cell responses in the absence of detectable viremia has not been elucidated yet. Additionally, HCMV is known to encode several gene products that potently inhibit T-cell recognition of infected cells. The best characterized are the four immune evasive US2, US3, US6 and US11 genes that with different mechanisms account for major histocompatibility complex (MHC) class I and class II degradation and intracellular retention in infected cells. By infecting M1 and M2 human macrophages (Mφ) with the wild type HCMV strain TB40E or a mutant virus deleted of the four immunoevasive genes US2, US3, US6 and US11, we demonstrated that human Mφ counteract the inhibitory potential of the US2-11 genes and remain capable to present peptides via MHC class I and class II molecules. Moreover, by sorting the infected and bystander cells we provide evidence that both infected and bystander Mφ contribute to antigen presentation to CD4+ and CD8+ T cells. The T cells responding to TB40E-infected Mφ show markers of the T effector memory compartment, produce interferon-γ and express the lytic granule marker CD107a on cell surface, thus mirroring the HCMV-specific T cells present in healthy seropositive individuals. All together our findings reveal that human Mφ escape inhibition of MHC-dependent antigen presentation by HCMV and continue to support T cell proliferation and activation after HCMV infection. Taking into account that Mφ are natural targets of HCMV infection and a site of viral reactivation from latency, our findings support the hypothesis that Mφ play crucial roles for the lifelong maintenance and expansion of HCMV-committed T cells in the human host.